(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
In the next few years, in the relations of most financial institutions between each other, as well as with customers, there will be a significant leap towards full “digitization”, which will turn banks into open “ecosystems”. This article discusses the digitalization of the banking sector, which can lead to positive effects, among which the authors note the formation of a common register in which banks will enter information about themselves and customers, as well as the possibility of obtaining data on the price of customer assets. Among other things, the plus will be the fact that all transactions will be registered in the registry and risks will be reduced in cooperation with an established circle of people, and when accounting for financial organizations, the probability of duplicate entries will be reduced to zero. Ultimately, digitalization will result in both counterparties (bank and client) not being able to take part in suspicious illegal transactions.